Kognition og narrativitet - Bundgård, Peer F. (K&K - Kultur og Klasse, 2006)
Det narrative skema som grundlæggende kognitivt skema Cognition and narrativity This paper aims at establishing the origin of the narrative schema in the perception of intentional movements. The distinction between mechanical and intentional movements is vital for human beings, and the narrative schema, which is underpinned by this distinction, is therefore claimed to be a basic cognitive principle of intelligibility. This is the reason why the narrative schema is by no means confined to the domain of the literary work of art or telling in general. It is rather a major principle for the combination of partial significations in many other domains. The paper explores the role traditionally assigned to the narrative schema within continental semiotics, and through an interpretation of Heider & Simmel’s study on apparent behavior it establishes the cognitive import of the narrative schema and its origin in visual perception; finally it gives examples of the meaning-organizing import of the narrative schema.